(untitled) (REMUNOM, 2024)
Uxi is a fruit originating from the Amazon, being abundant especially in the states of Pará and Amazonas, where it is widely consumed by the local population, fresh or as juice, sweets and other forms. This work aimed to develop and characterize in physical-chemical terms an uxi cream, in addition to carrying out a sensorial analysis of the product with a view to its acceptance. One hundred untrained tasters participated in the research, 43 women and 57 men, aged between 18 and 61 years. The cream had a high rate of general acceptance, and among men and women, being more accepted by men. Keywords: Amazon; fruit jam; Product of plant origin.